Gender wage gap and its effect on test scores of immigrant students - Eiji Yamamura (Osaka University, Institute of Social and Economic Research (ISER), 2016)
This paper examines how gender equality influences difference in cognitive skills between genders. For closer examination of Guiso et al. (2008), restricting the sample to immigrant allows us to reduce the possibility of reverse causality. Key findings obtained through regression estimation are: (1) decreased gender wage gap leads to girls exhibiting a reduced incidence of lateness and skipping school compared with boys, which in turn improves girls' test scores in mathematics, science, and reading; (2) the direct effect of the decreased wage gap on test scores exceeds its indirect effect on performance owing to influencing school attendance. Considering the direct and indirect effects of the wage gap: each 1% decrease in the wage gap results in a 0.20%, 0.13% or 0.06% increase in test scores for mathematics, science, and reading, respectively.
Keywords: D81; O11; Q54; Z13; 330; Gender gap index; Test scores; Mathematics; Immigrants